Geriatric Dysphonia: Characteristics of Diagnoses in Age-Based Cohorts in a Tertiary Voice Clinic. (May 2019) - Applebaum, Jeremy; Harun, Aisha; Davis, Ashley; Hillel, Alexander T.; Best, Simon R. A.; Akst, Lee M.
Objective: An aging population has increased focus on geriatric otolaryngology. Those ≥65 years old are not a uniform population, however, and recent gerontology literature recognizes important physiologic differences between the young-old (ages 65-74 years), middle-old (75-84), and old-old (≥85). This study evaluates differences within these groups among dysphonia patients ≥65 years relative to diagnosis and voice-related quality of life (V-RQOL). Methods: Chart review of all new patients ≥65 years presenting to the Johns Hopkins Voice Center between April 2015 and March 2017 identified chief complaint, diagnosis, and self-reported voice handicap. Etiology of dysphonia diagnoses were classified. Diagnostic categories and V-RQOL were evaluated as functions of patient age and gender. Results: Of 839 new patients ≥65 years, 463 (55.2%) reported chief complaint of dysphonia, with the most common etiologies being vocal fold immobility (28.3%) and atrophy (21.6%). Younger cohorts were more likely to present with benign vocal fold lesion and vocal fold immobility, while older cohorts were more likely to present with atrophy ( P = .016). The odds of having a diagnosis of vocal fold atrophy increased 7% with each year of life (odds ratio = 1.07; 95% CI, 1.03-1.11). V-RQOL scores were similar across gender and age categorization. Conclusion: Dysphonia patients ≥65 years are not a uniform group, and important differences exist in terms of diagnosis as a function of age. Knowledge of these differences may inform further investigations in the growing field of geriatric otolaryngology.